The Effect of Different Substrates on Laboratory Scale Cultivation of Sargassum cristaefolium - Waang, Dinda Christasya; Cokrowati, Nunik; Abidin, Zaenal (Journal of Coastal and Ocean Sciences, 2024)
Seaweed is an excellent aquatic commodity to be cultivated. One type is Sargassum cristaefolium, which contains alginate. Alginate is needed in various industrial fields for export and import. The high demand needs to be balanced by cultivation. One of the factors that affect cultivation is the substrate. The substrate as a habitat for seaweed is very diverse. This study aimed to analyze the best substrate for the growth of S.cristaefolium seaweed cultivated on a laboratory scale. This study was conducted for 20 days using a completely randomized design of 4 treatments and four repetitions to obtain 16 experimental units. The test treatments used were sand, coral, volcanic rock, and sand and coral substrates. The Anova test results showed that different substrates significantly affected the survival of S. cristaefolium. P2 with coral substrate gave the highest results for survival of 92.25%, final weight of 18.25 g, and alginate yield of 90%. This study concludes that the best substrate for the growth of S. cristaefolium is a coral substrate with survival reaching 91.25%, a final weight of 18.25 g, and an alginate yield of 90%.